THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) FOR ACQUIRING ENGLISH - HENDRA EKA PUTRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Information and communication technology is the study, development and application of computer-based information systems using telephones, televisions, radios, mobiles, computers and computer software to convert, store, process, protect and transmit information. This article focuses on the use of Information and Communication Technology (ICT) which can give valuable information and chance for language learners to acquire English language in real life.Kata kunci: Information and Communication Technology, acquiring English